REKA the best of architecture students work class of 2014 University of Malaya - Nur Mazidah Che Ghani; Asrul Sani A Razak; Naziaty Mohd Yaacob (Universiti Malaya Press, 2014)
The collection of student works from the second semester to introduce the curriculum, the formal and informal learning programmes whiew showcasing our students talent and work